(untitled) (Research, Society and Development, 2020)
Objective: to describe the experience of nursing students when taking the mandatory discipline Health of the Amazonian Populations, highlighting the results obtained through experiences provided to students by the discipline. Methodology: qualitative study, of a descriptive nature of the experience report type, in which the systematization of experiences was used, following the steps of starting point, initial questions, recovery of the lived process, background reflection and, finally, the point of arrival. Results: the academics were able to describe and point out the importance of insertion in indigenous health while undergraduate and how it will spread in the profession, focusing on investigating interculturality and intermedicality in different contexts among the national indigenous population. Conclusion: the use of the methodology was relevant, as it made it possible to describe the experience in a systematic way and helped the academics to reflect critically and reflexively on the knowledge of the operationalization of the service provided to the indigenous people.